Information Technology Governance Awareness: A Proposed Formula for Assessment - Uky Yudatama; Dwi Ekasari Harmadji (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2022)
This article aims to provide a proposed formula that can be used to measure the level of success in the practice of Information Technology Governance. To obtain this formulation, in-depth surveys and interviews involving several experts are needed. The calculation results show that organization G has an awareness value of 93 (good) with a maturity value of 3.13. On the other hand, organization E has an awareness value of 70 (medium) with a maturity value of 2.60. This proposed formula can be used as an alternative way to determine the level of success of an organization in the practice of Information Technology Governance by knowing the level of awareness. So far, to determine the level of success in implementing IT Governance practices in an organization, the method used is to calculate the maturity level that refers to COBIT best practices, which only focus on objects but do not focus on subjects (stakeholders) in the organization.